The effect of some types of the Lactic acid bacteria on some chemical and physiological changes in female rat’s blood - Salih AL-Doori, Salah Sadaim (The Iraqi Journal of Veterinary Medicine, 2012)
The effect of oral dosing of bacterial suspension of two types of lactic acid bacteria belonging to the genus lactobacilli that locally isolate on some biochemical and physiological criteria of female rats blood were studied. Three isolates of L. bulgarious and three isolates of L. delbeakli were obtained from the laboratories at the college of educationBreeding/university of Tikrit. Bacterial suspension given as a single oral dose of 2 ml(13 x 108 cell ml) for seven day. The results showed no significant changes P≥0.05 in at the blood physiological variables, especially hemoglobin (Hb) , packed cell volume (PCV) ,and total number of white blood cells (WBCs) , while there were significant reduction in the blood biochemical variables, particularly the level of cholesterol, and glucose, but there was no significant effect on some liver enzymes, compared with the values and the results of a group of control animals.